THE CHALLENGES OF EXTENDED CONFISCATION. DIRECTIVE 2014/42/EU AND TRANSPOSING DIFFICULTIES IN ROMANIA (EU and comparative law issues and challenges series (ECLIC), 2019)
A relatively new institution in Romanian criminal law, adopted in 2012 as a result of the imperative of transposing the international and European legal instruments of the last decades, the institution of “extended confiscation” has hardly found its place in the Romanian legal system, and it can be said that it conflicts with some traditional constitutional principles from which it is not possible to derogate. Thus, on the one hand, Romania has to respect its international commitments and, on the other hand, it must avoid violating some of the rights that have been hard-earned by Romanian young democratic constitutionalism. That is why the extended confiscation, this “necessary evil”, or compromise of modern criminal law, has already begun and we are sure it will generate in the future a lot of theoretical discussions and controversies, but it also encounters a certain retention of the practice, specific to all the innovative criminal law institutions. In the Romanian criminal system, extended confiscation is situated among the “safety measures”, near the “hospitalization based on mental illness” or “prohibition of practicing a profession”. As said in the legal text, the purpose for these measures, developed in the early 20th century by the Italian Positivist school, is the „social defence”. More precisely, it is about removing an existing “state of danger” and preventing the commission of future crimes. However, the extended confiscation is different. The goods so-called “proceeds of crime” do not have to be obtained directly from an offence for which the accused is convicted, but from a general unlawful conduct similar to that crime. I will observe, therefore, in the first chapter of my paper, the international context of fight against organized crime and its proceeds. After that, I will present the actual situation of the extended confiscation in Romania and its place between the criminal measures. In the next chapters I will insist on the concept of dangerousness and also observe the very little difference between the extended confiscation and a criminal punishment, because here we do not talk about the danger of some goods (as in the “classic” or the “common” confiscation, like drugs, guns), but about the danger of the detainer of those things. In the last chapter I will present the recent challenges in transposing the Directive 2014/42/ EU, especially regarding the standard of proof (beyond any doubt) and the recent unconstitutional decision in this case.